The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2337/db11-1141
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of Mesenchymal Stem Cells Ameliorates Hyperglycemia in Type 2 Diabetic Rats

Abstract: Infusion of mesenchymal stem cells (MSCs) has been shown to effectively lower blood glucose in diabetic individuals, but the mechanism involved could not be adequately explained by their potential role in promoting islet regeneration. We therefore hypothesized that infused MSCs might also contribute to amelioration of the insulin resistance of peripheral insulin target tissues. To test the hypothesis, we induced a diabetic rat model by high-fat diet/streptozotocin (STZ) administration, performed MSC infusion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
242
4
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(279 citation statements)
references
References 40 publications
12
242
4
3
Order By: Relevance
“…IRS-1, PDK1, and PKCζ are also important for conferring insulin signaling transduction and glucose uptake besides protein kinase Akt [40]. This result was consistent with Si' study, which found MSC infusion could restore the concentration of total GLUT4 and promote GLUT4 translocation to the cell memberane [23].…”
Section: Conflict Of Interestsupporting
confidence: 81%
See 2 more Smart Citations
“…IRS-1, PDK1, and PKCζ are also important for conferring insulin signaling transduction and glucose uptake besides protein kinase Akt [40]. This result was consistent with Si' study, which found MSC infusion could restore the concentration of total GLUT4 and promote GLUT4 translocation to the cell memberane [23].…”
Section: Conflict Of Interestsupporting
confidence: 81%
“…In the present study, we induced T2DM in a rat model by a high-fat diet combined with STZ administration and performed ASC infusion at the 28 th day after STZ injection. We found that ASC infusion could effectively ameliorate hyperglycemia in T2DM rats, which was consistent with other reports [1,2,23]. Furthermore, our results of hyperinsulinemic-euglycemic clamp studies demon-INSR in skeletal muscle and adipose and liver tissues after therapy to investigate the possible mechanisms involved in the effect of ASC infusion on insulin sensitivity.…”
Section: A B Csupporting
confidence: 80%
See 1 more Smart Citation
“…In human diabetic foot ulcers, implantation of autologous BM-MSCs signifi cantly improves clinical parameters such as ulcer size and pain-free walking distance [ 97 ] . Apart from accelerating wound healing, infusion of MSCs has been shown to reverse diabetic symptoms in type 2 diabetic rodents [ 98 ] . In other studies, combination protocols of antioxidant agents, such as epigallocatechin-3-gallate (EGCG), along with MSCs promote wound healing by modulating chronic infl ammation [ 99 ] .…”
Section: Challenges and Perspectives In The Treatment Of Chronic Wounmentioning
confidence: 99%
“… Diabetic + Stem cell (STZ+ MSCs) group: 10 diabetic rats received i.v. injection (through tail vein) of 2 × 10 6 MSCs suspended into 0.2 mL physiological saline for each rat [20], for one time [21] . Similarly, for the control group and diabetic group, 0.2 mL of physiological saline was injected instead of MSCs.…”
Section: Bm-mscs Injection and Experimental Designmentioning
confidence: 99%